2017
DOI: 10.1111/ases.12398
|View full text |Cite
|
Sign up to set email alerts
|

Case of giant paraesophageal hiatal hernia associated with Morgagni hernia

Abstract: Simultaneous paraesophageal and Morgagni hernias are very rare. Here, we report a case involving a 91-year-old woman with simultaneous paraesophageal and Morgagni hernias. Both hernias were repaired laparoscopically. The postoperative course was uneventful. Laparoscopic repair for hernias seems to be feasible and minimally invasive, but only a few reports have described such repairs of hernial orifices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A unifying feature of the few previously reported cases of concurrent paraesophageal and Morgagni hernias is the presence of chest pain, gastrointestinal complaints, or both [6]. This case differs in that our patient denied either angina or gastrointestinal discomfort and instead presented with elusive atypical paroxysms of cough-associated syncope.…”
Section: Commentmentioning
confidence: 53%
“…A unifying feature of the few previously reported cases of concurrent paraesophageal and Morgagni hernias is the presence of chest pain, gastrointestinal complaints, or both [6]. This case differs in that our patient denied either angina or gastrointestinal discomfort and instead presented with elusive atypical paroxysms of cough-associated syncope.…”
Section: Commentmentioning
confidence: 53%
“…The technique of intracorporeal mesh closure has been proven to reduce recurrence of the hernia and adhesions, gaining space in these repairs. 9,13 Reports of MH correction by such a pathway in advanced age patients reiterate their safety, combined with a prior analysis -minute operation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The patient of the case did not present any risk factor for the increase of this pressure, which reiterates its congenital origin. 8,14,15 Due to cardiorespiratory discomfort and gastrointestinal manifestations, diagnosis and treatment in childhood become more prevalent, making the diagnosis in adult life uncommon, with reports of a higher incidence in females in more than 50% of cases and the mean of age of the diagnosis of 53 years. The clinical picture varies according to the size of the defect and herniated organ, and, unlike the child, the symptoms are chronic, and may present with nausea, vomiting, anorexia, abdominal pain, chest pain, dyspnea, dyspepsia or even asymptomaticthe absence of symptoms due to the fact that the organs are commonly lined by the parietal peritoneum of the hernia sac.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have reported acute complications of giant hiatal hernia such as acute gastric volvulus, intrathoracic gastric perforation, and incarcerated obstruction of the herniated viscera (8,13,22,23). Romano et al demonstrated the length of stay and mortality of elderly patients was obviously increased in a non-elective giant hiatal hernia repair group compared with an elective repair group (24).…”
Section: Discussionmentioning
confidence: 99%